Low-coverage whole genome sequencing of eleven species/subspecies in Dioscorea sect. Stenophora (Dioscoreaceae): comparative plastome analyses, molecular markers development and phylogenetic inference - Hu, Ke; Sun, Xiao-Qin; Chen, Min; Lu, Rui-Sen (Frontiers in Plant Science, 2023)
Dioscorea sect. Stenophora (Dioscoreaceae) comprises about 30 species that are distributed in the temperate and subtropical regions of the Northern Hemisphere. Despite being evolutionarily “primitive” and medically valuable, genomic resources and molecular studies of this section are still scarce. Here, we conducted low-coverage whole genome sequencing of 11 Stenophora species/subspecies to retrieve their plastome information (whole plastome characteristics, plastome-divergent hotspots, plastome-derived SSRs, etc.) and polymorphic nuclear SSRs, as well as performed comparative plastome and phylogenetic analyses within this section. The plastomes of Stenophora species/subspecies ranged from 153,691 bp (D. zingiberensis) to 154,149 bp (D. biformifolia) in length, and they all contained the same 114 unique genes. All these plastomes were highly conserved in gene structure, gene order and GC content, although variations at the IR/SC borders contributed to the whole length differences among them. The number of plastome-derived SSRs among Stenophora species/subspecies varied from 74 (D. futschauensis) to 93 (D. zingiberensis), with A/T found to be the most frequent one. Seven highly variable regions and 12 polymorphic nuclear SSRs were identified in this section, thereby providing important information for further taxonomical, phylogenetic and population genetic studies. Phylogenomic analyses based on whole plastome sequences and 80 common protein coding genes strongly supported D. biformifolia and D. banzhuana constituted the successive sister species to the remaining sampled species, which could be furtherly divided into three clades. Overall, this study provided a new perspective for plastome evolution of Stenophora, and proved the role of plastome phylogenomic in improving the phylogenetic resolution in this section. These results also provided an important reference for the protection and utilization of this economically important section.